2009
DOI: 10.1097/hjh.0b013e32831e4599
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance-derived aortic distensibility: validation and observed regional differences in the elderly

Abstract: Cardiovascular magnetic resonance-derived aortic distensibility is an accurate measure of arterial stiffness and can evaluate regional stiffness through the aorta. Furthermore, our results suggest that aortic stiffening may preferentially occur in the proximal aortic segments in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 31 publications
4
51
1
1
Order By: Relevance
“…[12], Flow mediated dilatation (FMD) and whole body arterial compliance (WBAC) [8]. There are many studies showing similar results using central artery compliance by invasive procedures (mean arterial pressure, aortic augmentation index (AIx) and central systolic blood pressure (SBP) [7,13] and non invasive techniques (MRI and USG) [14,15]. But contrary to our study some of the studies have not shown change in peripheral arterial compliance during different phases of menstrual cycle [7,16].…”
Section: Resultscontrasting
confidence: 49%
“…[12], Flow mediated dilatation (FMD) and whole body arterial compliance (WBAC) [8]. There are many studies showing similar results using central artery compliance by invasive procedures (mean arterial pressure, aortic augmentation index (AIx) and central systolic blood pressure (SBP) [7,13] and non invasive techniques (MRI and USG) [14,15]. But contrary to our study some of the studies have not shown change in peripheral arterial compliance during different phases of menstrual cycle [7,16].…”
Section: Resultscontrasting
confidence: 49%
“…Assessing, not only cardiac, but also, vascular structure and function, CMR has substantially greater accuracy and reproducibility for the assessment of cardiac indices compared with alternative methodologies, such as echocardiography. [10][11][12][13][14][15][16] Importantly, CMR can assess aortic stiffness, which has proven prognostic significance in patients with chronic kidney disease (CKD). 14,17,18 Furthermore, this imaging modality can assess peripheral arterial diameter and flow -allowing the serial evaluation of alterations in brachial artery flow induced by distal AVF-formation, as well as evaluation of peripheral artery endothelial function -by a standard flow-mediated dilatation technique.…”
mentioning
confidence: 99%
“…A final True-FISP cine image was then acquired at the level of the distal descending aorta (DDA), 5-10 cm distal to the diaphragm, as previously described. 15 Brachial artery blood pressure was taken concurrently, using a magnetic resonance imaging-compatible automated noninvasive sphygmomanometer, with the results of three measurements averaged.…”
mentioning
confidence: 99%
“…Our values for traditionally measured circumferential ascending aortic area strain, uncorrected for longitudinal strain, and for descending aortic area strain were comparable to those reported in similarly aged studies that found reversal of the normal proximal-to-distal aortic stiffness gradient. 9,10 The observation of markedly higher stiffness in the ascending as compared to the descending aorta, which is only a dozen centimeters downstream, 17 is not supported by studies of regional transit time PWV, which found a persistent positive stiffness gradient moving distally along the aorta in older people. 18 After adjusting for longitudinal strain, circumferential strain in the ascending aorta was comparable to strain in the descending aorta, which suggests that with age, proximal Figure 7.…”
Section: Discussionmentioning
confidence: 87%
“…7,8 We hypothesized that longitudinal strain in the proximal ascending aorta confounds circumferential area measurements and results in marked and variable underestimation of strain and overestimation of stiffness, particularly in older cohorts where circumferential strains are small. 9,10 To test this hypothesis, we examined longitudinal strain in the proximal aorta, and circumferential strains in the proximal ascending and descending thoracic aorta during the cardiac cycle in a community-based sample of older men and women.…”
mentioning
confidence: 99%